The Case for Onloading Continuous High-Datarate Perception to the Phone - Han, Seungyeop; Philipose, Matthai (Proceedings of HotOS'09: 14th Workshop on Hot Topics in Operating Systems, 2013)
Much has been said recently on off-loading computations from the phone. In particular, workloads such as speech and visual recognition that involve models based on “big data” are thought to be prime candidates for cloud processing. We posit that the next few years will see the arrival of mobile usages that require continuous processing of audio and video data from wearable devices. We argue that these usages are unlikely to flourish unless substantial computation is moved back on to the phone. We outline possible solutions to the problems inherent in such a move. We advocate a close partnership between perception and systems researchers to realize these usages.